Әлеуметтендіру арқылы жеке тұлғаны қалыптастыру жолдары - Бақытжанқызы, С. (My University, 2013)
These reports are intended for students and teachers of pedagogical college. In these reports is supplied the information about the directions of socialization, about norms and values of modern society. Process of socialization can be opened by means of the following processes: adaptation, integration, self-development, self-knowledge. Pedagogical bases of socialization of the personality have to be connected with age and psychological features. Educational work takes place in groups on the basis of the following directions: "Family", "Collective", "Society", "World", "I am a personality".